Across the great divide: reflecting on dual positions in clinical psychology to enhance equality and inclusion between those working in and those referred to services. Issue 6 (2nd November 2018) - Keville, Saskia
ABSTRACT: In the United Kingdom there are guidelines and policies to facilitate boundaries within professional interactions which recognise power differences between those employed in services and those referred to them. However, perhaps we must acknowledge that these boundaries may have indirectly resulted in an unbridgeable division between professionals and those that use services in current professional policies. This paper considers what it means to be a Clinical Psychologist and user of services or carer with the complexity that surrounds this dual position. Through incorporating personal reflections, it seeks to highlight how hard it can be to break down 'them and us' barriers despite the best intentions of the profession and policy makers. The suggestion is that to be truly equal and inclusive we must shift from relating differently to service users, professionals and professionals who may use services by acknowledging our personal positions; otherwise breaking down barriers will remain an ideal rather than a reality. When it comes to our overall well-being breaking down these barriers could shift us from direct or oblique misunderstandings, judgements and stigma towards understanding, tolerance and acceptance within and between all of us.